1975
DOI: 10.1149/1.2134060
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Deposition of Metal Nitrides by Thermal Decomposition of Organometallic Compounds

Abstract: Decomposition reaction of dialkylamides of boron, silicon, tin, titanium, zirconium, niobium, and tantalum was investigated. The amides of transition metals decomposed to the corresponding nitrides at 300~176 whereas those of boron, silicon, and tin yielded elemental deposits at higher temperatures. In the deposition of titanium nitride from titanium tetrakis(dimethylamide), two optimum temperatures at 400 ~ and at 800~ in nitrogen or hydrogen atmosphere were found, but in argon only low temperature deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(47 citation statements)
references
References 6 publications
1
45
0
Order By: Relevance
“…Furthermore, there is a parent chemistry between amido complexes of Ti and Cr and it has been found that films deposited using Ti(NMe2)4 [60,61] and Ti(NEt2)4 [61] are heavily contaminated with carbon that is consistent with our prediction using the chromium derivative. In fact, reasonably pure metal nitride films prepared using tetrakis(dia1kyamido)metal complexes requires addition of NH3.…”
Section: Totai Pressure (Atm)supporting
confidence: 87%
“…Furthermore, there is a parent chemistry between amido complexes of Ti and Cr and it has been found that films deposited using Ti(NMe2)4 [60,61] and Ti(NEt2)4 [61] are heavily contaminated with carbon that is consistent with our prediction using the chromium derivative. In fact, reasonably pure metal nitride films prepared using tetrakis(dia1kyamido)metal complexes requires addition of NH3.…”
Section: Totai Pressure (Atm)supporting
confidence: 87%
“…5 Such amidochromium compounds are not suitable single sources for the growth of chromium nitride coatings since the films are heavily contaminated with carbon. Similarly, in spite of a MN x cluster core, transition-metal dialkylamido compounds, M(NR 2 ) x , were not successfully used as singlesource precursors for the growth of metal nitride, since large amounts of carbon were incorporated into the films, as reported for titanium 6,7 and vanadium. 8 Therefore, deposition of metal nitrides using these precursors requires addition of a large excess of ammonia, as demonstrated for nitrides of titanium, [9][10][11][12][13][14][15][16][17] 18 This MOCVD reaction with NH 3 has been widely investigated in order to understand the formation of nitride 9,10,13-17 but pyrolysis of M(NR 2 ) x without any additive is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…8 Therefore, deposition of metal nitrides using these precursors requires addition of a large excess of ammonia, as demonstrated for nitrides of titanium, [9][10][11][12][13][14][15][16][17] 18 This MOCVD reaction with NH 3 has been widely investigated in order to understand the formation of nitride 9,10,13-17 but pyrolysis of M(NR 2 ) x without any additive is still unclear. 6,7,16,17,20,21 In this paper, the tetrakis(diethylamido)chromium(IV) complex, Cr(NEt 2 ) 4 (1), has been employed as single-source precursor to deposit chromium carbonitride thin films by MOCVD. The results are compared with thermodynamic calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Low deposition temperatures have been obtained by utilizing very reactive feed gases (TiC1 4 with NH 3 1 , or organometallic compounds 2 ) at atmospheric pressure or by excited state chemical reactants created in a low pressure plasma. 3 -8 A major goal of these efforts is to develop a hybrid process which combines the advantages of CVD (uniform coverage, relatively minor substrate preparation) and that of physical vapor deposition (PVD) processes (low substrate temperature).…”
Section: Perature ( <600°c) Chemical Vapor Deposition (Cvd) Methods Hmentioning
confidence: 99%